The Curriculum Development of Enhancing Research in Classroom Competence through E-classnet for Teacher Training Student at Faculty of Education, Souphanouvong University - VATHANAVONG , Phaivanh; VATHANAVONG , Thongthiane; SANRATTANA, Unchalee; YUANKRATHOK, Panadda (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research was the development of a supplementary curriculum, which is part of the research task for doctoral studies. The purposes of this research were to: 1) to study the state of the problems and needs assessment for research in classroom through the E-Classnet system and 2). To design and examine the quality of the curriculum to enhancing research in classroom competence through the E-Classnet system for teacher training student at faculty of education, Souphanouvong University. Four steps were used as the development process of the curriculum, including a study of the fundamental data, design and examine quality of the training curriculum, implementation and improvement of the training curriculum respectively. Using mixed methods research process and internal support with qualitative and quantitative methods. The samples were teachers and 4th year students under the faculty of education, Souphanouvong University in the first semester of the academic year 2020-2021, including 56 people. Instruments used to collect the data were questionnaire on the state and needs assessment, comment record form. The statistical analysis was percentage, mean, standard deviation, contents analysis, modified priority needs index (PNImodified). The results of this research were as follows: 1). The state of practicing on research in classroom was moderate ; While the expected or expected state or needs assessment for curriculum development is at a much-level by the PNI = 0.201. Comparing the differences in needs assessment for Curriculum development by gender, age, programs, the teaching experience, the advisors and the assistants’ advisors as a whole did not differ at the .05 level with statistical significance. 2). The Curriculum of enhancing research in Classroom competence through E-classnet for Teacher training students at Faculty of Education, Souphanouvong University were designed comprising of 7 articles and 10 lesson plans that used through the E-Classnet system. And, 0.82 of the consistency index with much-levels of the suitability evaluation from 5 experts. Therefore, this curriculum had much quality and to be implemented in the next step.